2024
DOI: 10.1021/acs.nanolett.4c00687
|View full text |Cite
|
Sign up to set email alerts
|

Large and Pressure-Dependent c-Axis Piezoresistivity of Highly Oriented Pyrolytic Graphite near Zero Pressure

Bingjie Wang,
Juyao Li,
Zheng Fang
et al.

Abstract: The c-axis piezoresistivity is a fundamental and important parameter of graphite, but its value near zero pressure has not been well determined. Herein, a new method for studying the c-axis piezoresistivity of van der Waals materials near zero pressure is developed on the basis of in situ scanning electron microscopy and finite element simulation. The c-axis piezoresistivity of microscale highly oriented pyrolytic graphite (HOPG) is found to show a large value of 5.68 × 10 −5 kPa −1 near zero pressure and decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Two-dimensional (2D) materials have garnered significant attention owing to their unique structure—a 2D hexagonal lattice composed of carbon atoms—which imparts remarkable electronic properties to them [ 1 , 2 , 3 , 4 , 5 ]. In addition, the atomical thinness of 2D materials endows them with exceptional flexibility and mechanical deformability, further enabling the manipulation of their electronic structure through strain engineering methods [ 5 , 6 , 7 , 8 , 9 , 10 ]. For instance, it has been found that out-of-plane deformation can induce local changes in the electronic properties of graphene [ 9 , 10 ], leading to a shift in the electron’s Bloch wave vector, akin to the behavior observed in the presence of an external magnetic field [ 4 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) materials have garnered significant attention owing to their unique structure—a 2D hexagonal lattice composed of carbon atoms—which imparts remarkable electronic properties to them [ 1 , 2 , 3 , 4 , 5 ]. In addition, the atomical thinness of 2D materials endows them with exceptional flexibility and mechanical deformability, further enabling the manipulation of their electronic structure through strain engineering methods [ 5 , 6 , 7 , 8 , 9 , 10 ]. For instance, it has been found that out-of-plane deformation can induce local changes in the electronic properties of graphene [ 9 , 10 ], leading to a shift in the electron’s Bloch wave vector, akin to the behavior observed in the presence of an external magnetic field [ 4 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%